The International Livestock Centre for Africa (ILCA) and food production in Africa - Brumby, P.J. (Elsevier, 1984)
Discusses the generally low level of food supplies in Africa, mentioning the importance of crop-livestock associations in tackling the problem; and examines research, documentation and training activities of ILCA.